Efficacy of Some Insect Growth Regulators (IGR) Against Jasmine White Fly Alearoclava Jasimini ( Homoptera: Aleyrodidae) on Citrus Tree - Taha, H. A.; Adeal, L.; Hussam, M.S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The efficacy of five insect growth regulators has been tested against white fly larva Alearoclava jasimini on citrus tree orchards. Data from field tl'ia ls con finned that percent mortalities were 43.7, 33.9, 23.7, 20.8 and     12.3  for  Admiral ( I miL)  pyriproxefen, Nomol t  1 5 SC  (!milL) Teflubenzuren , Match 050 EC (  I milL ) Lufenuren , cascade I 0 F.C (0.9mi/L) flufenoxaron, and Dimiline 10 EC ( I milL)  Difluben- zuron. The result indicated that Admiral and Nomolt have a continuous  effect for one month , so the treatment needs to be repeated for each four weeks. Also, Admiral and Nomolt effect against eggs hatching by 41. 3 % and• 9 %, respectively .